Description and treatment of evergreens - Oman, Andrew Edward (My University, 1900)
Introduction: The subject evergreens is at once of interest, for it suggests trees of durable beauty. Be it in summer or in winter, evergreens stand clothed in their never failing verdure. With the winter snow bearing down heavily upon their persistent foliage, they help to offset the bleak and barren aspect of a lawn or landscape during the winter condition. The study of this class of trees, then brings us into a broad field. It brings us to the consideration of the Natural Order Coniferae, the genera, which, with their many species, would require pages to tabulate. This treatise, therefore, will be limited to the evergreens represented on our college campus, and the following synopsis, taken from Hoopes “Book of Evergreens”, and will be the basis for the present discussion.
Citation: Oman, Andrew Edward. Description and treatment of evergreens. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Evergreens; Horticulture; Forestry; Theses